2019
DOI: 10.3389/fncel.2019.00234
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Spectrins: Nanoscale Organization, Functional Domains and Spectrinopathies

Abstract: Spectrin cytoskeletons are found in all metazoan cells, and their physical interactions between actin and ankyrins establish a meshwork that provides cellular structural integrity. With advanced super-resolution microscopy, the intricate spatial organization and associated functional properties of these cytoskeletons can now be analyzed with unprecedented clarity. Long neuronal processes like peripheral sensory and motor axons may be subject to intense mechanical forces including bending, stretching, and torsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 95 publications
(154 reference statements)
0
15
0
Order By: Relevance
“…New perturbation strategies with better molecular, spatial and temporal specificity such as optically-driven inhibitors will allow to dissect the role of the MPS in axonal physiological processes, before zooming out to assess the consequences on neuronal connectivity and information processing. Finally, potential dysfunctions of the MPS in neuropsychiatric diseases, from spectrinopathies [68,69] to Alzheimer's disease, remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…New perturbation strategies with better molecular, spatial and temporal specificity such as optically-driven inhibitors will allow to dissect the role of the MPS in axonal physiological processes, before zooming out to assess the consequences on neuronal connectivity and information processing. Finally, potential dysfunctions of the MPS in neuropsychiatric diseases, from spectrinopathies [68,69] to Alzheimer's disease, remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that cortical spectrin is more prominent towards the apical surface of MBE-F cells (Figure 1). These observations are perhaps not surprising considering spectrin is a multifunctional protein that is important not only for providing strength and stability to the plasma membrane [51,52] and organisation of cytoskeleton [44], but also plays an important role in cell polarity [53], regulation of ion channels [54], and assembly of excitable axon domains [55]. It is well established that the spectrin meshwork under the plasma membrane of erythrocytes hinders the release of plasma membrane EVs [24].…”
Section: Discussionmentioning
confidence: 99%
“…Other neuronal CaMBPs expressed in the hippocampus, such as myosin light chain kinase [ 97 , 98 ], spectrin [ 99 ], and fodrin [ 100 ], play major roles in the cytoskeleton structure and dynamics, and they also play key roles in neuronal activity and interneuronal connectivity. In addition, Ras-guanine nucleotide-releasing factor 1 (Ras-GRF1), which is also expressed in CA1 neurons of the hippocampus, has been shown to be involved in the induction of LTP and LTD associated with spatial learning and long-term memory [ 101 , 102 ].…”
Section: The Roles Of Cam In Neurons As Cytosolic Calcium Buffering and Calcium Signaling Molecule—subcellular Distribution Of Cam-bindinmentioning
confidence: 99%